Entrepreneurship and Small Island Economies - Pounder, Paul; Gopal, Naresh (Organizations and Markets in Emerging Economies, 2021)
Over the past two decades, the study of entrepreneurship and its importance to the economy has increased in appeal to academics, practitioners and governments. This study explores entrepreneurship in small island economies within regions based on Total Entrepreneurial Activity (TEA) and Established Business Ownership (EBO) as observed in the Global Entrepreneurship Monitor (GEM) dataset. This research uses the pooled regression model to study the impact of TEA and EBO on economic growth. The findings highlight that new venture creation is a driver that improves gross domestic product (GDP); however, there are significant differences across SIDS in the orientation of TEA and EBO that suggest that other contextual issues like culture, education system, and entrepreneurial support elements influence entrepreneurial behaviour across regions as well. The more advanced of these nations like Singapore and Puerto Rico benefit from knowledge networks and scientific mobility, while the smaller economies in the Caribbean and Pacific Region show less openness to pursuing entrepreneurial endeavours. These findings provide a foundation for further research on varying types of combinations of both economic factors and contextual differences that lend to the transitioning process towards an emerging economy.
Keywords: entrepreneurship; total entrepreneurial activity,; established business ownership; economic development; SIDS